Maxillary ameloblastoma mimicking an oroantral fistula - (:unkn) unknown (Springer Verlag, 2013)
Background: The aim of this current report is to present an unusual case of a maxillary ameloblastoma mimicking an oroantral fistula. Case report: A left subtotal maxillectomy via Weber-Ferguson-type incision was performed. The patient tolerated the procedure well, the postoperative course was uneventful, and the patient was discharged 3 days after surgery with a mild paraesthesia of the right infraorbital nerve distribution. The infraorbital nerve paraesthesia has resolved 5 months after resection. The patient has been followed-up for 3 years without recurrence. Discussion: Ameloblastoma is a well-known pathology of the maxillofacial region. However, unusual manifestations of this tumor can represent a serious challenge for diagnosis. © 2012 Springer-Verlag.
Keywords: Ameloblastoma; Maxilla; Oroantral fistula; Weber-Ferguson